Analysis Of The Election Supervision System In Indonesia: A Comparison Between Simultaneous And Non-Simultaneous Elections - Kausar Jumahir Lesen (Cita konsultindo, 2025)
This article will describe the various forms of the election oversight system in Indonesia, starting from the Old Order era to reform (from Panwaslak to Bawaslu; from Pilkada not simultaneously and concurrently). However, there are various kinds of problems in the supervision of elections in Indonesia, including manipulation of nomination requirements, invalidity of voter data, money politics in campaigns, abuse of authority and intervention of power structures, as well as inflating the results of vote acquisition as a common phenomenon in almost every election implementation, which involves election organizers, election participants and/or the public as voters. Thus, the existence of election supervisors in political and administrative law reviews is important to avoid delegitimizing the election process and results, as well as anticipating the development of various acts of election violations, in order to strengthen public confidence in various problems in the electoral system. The existence of strong election supervisors is inseparable from the importance of oversight mechanisms for the realization of quality elections 5